BENTUK PARTISIPASI MASYARAKAT DALAM PENGELOLAAN SAMPAH DI KECAMATAN BANJARMASIN BARAT - Murnika Murnika; Ghinia Anastasia Muhtar (KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to determine the form of community participation in waste management in West Banjarmasin District. This research method uses quantitative descriptive with a sampling technique using purposive sampling with a total of 100 respondents from the total population of the people of West Banjarmasin District. Data was collected through the distribution of questionnaires. Based on the results of the analysis, the highest form of participation is known to be in the form of physical or energy (64.3%) in the high category. Following below it, participation in the social form (52.5%) and property participation (50.96%) which are included in the medium group. Participation in the form of thoughts (33.6%) and participation in the form of skills (26.13%) are included in the low category.